Training load differences between position and set in NCAA D1 collegiate women`s volleyball match - Brojanac, A. P.; Clark, D.; Munger, K.; Sekiguchi, Y. (International Journal of Exercise Science Conference Proceedings, 2025)
PURPOSE: This study investigated the training load differences between positions and sets in NCAA DI collegiate women`s volleyball matches.